2019
DOI: 10.1002/path.5290
|View full text |Cite
|
Sign up to set email alerts
|

Effect of FGF/FGFR pathway blocking on lung adenocarcinoma and its cancer‐associated fibroblasts

Abstract: Cancer‐associated fibroblasts (CAFs) are known to promote tumourigenesis through various mechanisms. Fibroblast growth factor (FGF)/FGF receptor (FGFR)‐dependent lung cancers have been described. We have developed a mouse model of lung adenocarcinoma that was constructed through the induction of Fgf9 overexpression in type 2 alveolar cells. The expression of Fgf9 in adult lungs resulted in the rapid development of multiple adenocarcinoma‐like tumour nodules. Here, we have characterised the contribution of CAFs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 39 publications
3
35
1
Order By: Relevance
“…Increased expression of HPA in pancreatic cancer cells may disrupt the extracellular matrix (ECM) and basement membrane (BM), thus creating favorable conditions for the invasion and migration of pancreatic cancer cells (7,8). Recently, the role of fibroblast growth factor 2 (FGF2) in the development and progression of malignant cancer types has attracted great interest (9). The binding of FGF2 to its receptor, fibroblast growth factor receptor 2, may lead to the activation of tumor-related signaling pathways, thus increasing cell proliferation, migration and invasion (10).…”
Section: Introductionmentioning
confidence: 99%
“…Increased expression of HPA in pancreatic cancer cells may disrupt the extracellular matrix (ECM) and basement membrane (BM), thus creating favorable conditions for the invasion and migration of pancreatic cancer cells (7,8). Recently, the role of fibroblast growth factor 2 (FGF2) in the development and progression of malignant cancer types has attracted great interest (9). The binding of FGF2 to its receptor, fibroblast growth factor receptor 2, may lead to the activation of tumor-related signaling pathways, thus increasing cell proliferation, migration and invasion (10).…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the frequency of STK11 mutations in NS-NSCLC patients seems to be lower (4% in Asians) or higher (25% in African Americans) according to the populations, and comparative to the incidence observed in Caucasians (around 14%) [53,316,317]. To detect genomic alterations in fibroblast growth factor receptor (FGFR), biomarkers have been developed but their therapeutic application is still preliminary and concerns mostly squamous cell carcinomas of the lung [318][319][320][321][322].…”
Section: Others Potential Biomarkers Of Interestmentioning
confidence: 99%
“…Research on a mouse model of lung adenocarcinoma showed that FGF released by CAF induced TAM recruitment. Blocking of FGF receptor (FGF-R) with the Fgfr tyrosine kinase family inhibitor AZD4547 showed strong TAM abolishment and tumor regression, making this receptor a potential therapeutic target [102]. In addition, targeting other important molecules for monocyte/macrophage recruitment in cancer, i.e., catecholamines by 6-hydroxydopamine [103] and complement components such as C5a, may also be promising in cancer treatment [104].…”
Section: Tamsmentioning
confidence: 99%